RESPON PERTUMBUHAN TANAMAN MELON (Cucumis melo L.) TERHADAP PEMBERIAN MEDIA TANAM DAN PUPUK ORGANIK CAIR MAJA (Aegle marmelos L.) - Army Dita Serdani; Palupi Puspitorini; Agung Setya Wibowo; Intan Fuji Ariani (Universitas Tribhuwana Tunggadewi, 2020)
Melon (Cucumis melo L) is a horticultural plant that has the potential to be developed and cultivated by farmers. The high productivity of melon plants is influenced by good cultivation methods, namely the addition of planting media and liquid organic fertilizer. The purpose of this study was to determine the effect of various concentrations of planting media and liquid organic fertilizer of Maja fruit on the growth and yield of melons. The research was conducted from April to June 2020 in Sukorejo Village, Blitar Regency with a height of 180 meters above sea level. This study used a factorial randomized block design (RBD) consisting of two factors, repeated 3 times. Parameters observed were plant height, stem diameter, fruit weight, fruit thickness, and fruit diameter. The data obtained were analyzed using analysis of variance (F test). The first factor is the planting medium and the second factor is liquid Maja fertilizer. Based on the results of research is the combination of planting medium bokashi, husk charcoal, cocopeat, and NPK fertilizer and 250 ml/plant (M1P2) liquid organic fertilizer was the best treatment combination to increase the growth and yield of melon plants. The height parameters showed the best results at 5 MST observations of 190, 81 cm; fruit weight of 2.042 gram; fruit diameter 17 cm; and fruit thickness reaching 5.29 cm.